Assessing the impact of mega-city construction engineering on urban livability: an explorative study of Yan'an - Liu, Lei; Zhang, Lanyue; Guo, Yimeng; Ren, Keang (Frontiers in Public Health, 2024)
Yan'an City is a typical squeezed city in China and faces the challenge of limited living space. The adoption of the “Mountain Excavation and City Construction (MECC)” program was poised to elevate the city's livability. Despite the importance of megacity construction projects, few studies have examined their impact on urban livability. This study aims to fill this gap by analyzing the effects of MECC and the satisfaction characteristics of urban livability in Yan'an City, based on survey data from both old and new urban areas. Employing factor analysis and multiple linear regression, this paper assesses the influence of MECC on urban livability across different demographic groups, including age, educational background, and occupation. The empirical findings demonstrate a significant positive effect of the MECC project on urban livability. However, during categorization discussions, some respondents expressed concerns about its negative impact. The results of multiple linear regression indicate that factors such as career prospects, residential satisfaction, interpersonal relationships, and transportation level significantly influence livability (R2 = 0.607 in ND and R2 = 0.609 in OD).